The morphological, karyological and phylogenetic analyses of three Artemisia L. (Asteraceae) species that around the Van Lake in Turkey - Sancar, Pelin Yilmaz; Civelek, Semsettin; Kursat, Murat (Firenze Univ Press, 2021)
Artemisia is one of the biggest genera in the family Asteraceae, with around 500-600 taxa at specific and sub-specific levels and organised in five subgenera. Due to the high number of taxa, a lot taxonomists are trying to solve the problem of its classification and phylogeny but its natural classification still has not been achieved. The aim of this study is to try to solve the problematic systematic relationship between three different Artemisia species growing in close proximity to each other in the light of morphological, karyological and molecular data. The roots, stems, leaves, flowers structures of the plant samples collected from different populations belong to these species were investigated within the framework of morphological studies. Additionally, the chromosome counts and karyotype analysises of these species were made and idiograms were drawn in the karyological studies. In the context of phylogenetic studies, ITS (ITS1-5.8S-ITS2) and trnT - trnL3' regions of 22 individuals belonging to 3 taxa were studied. According to results of phylogenetic anlysis, it has been found that there is completed speciation genetic isolation mechanism between the species Artemisia spicigera, Artemisia taurica and Artemisia fragrans that inhibit gene flow. Also Artemisia fragrans and Artemisia spicigera species are very similar to each other in terms of morphological characteristics. However, since populations of the species Artemisia fragrans are autopolyploid, the dimensional values of their morphological squares are larger than those of the species Artemisia spicigera. This study is important as it is the first molecular based study relating with some species of Artemisia growing naturally in Turkey.
Keywords: Artemisia; karyology; morphology; phylogeny; cpDNA trnT-trnL3'; r-DNA ITS